2019
DOI: 10.22605/rrh5240
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the sexual and reproductive health knowledge of adolescent mothers from indigenous populations in Ratanak Kiri Province, Cambodia

Abstract: Background: Female adolescents undergo drastic changes in their bodies during puberty. Therefore, they need to be informed about these pending changes at an early age so they can build a foundation for healthy reproductive behaviour. This study explored young female adolescents' understanding of pubertal body changes and knowledge of their reproductive system. Method: Female students in grades seven, eight and nine were recruited from eight junior high schools in Kupang, Indonesia. Body mapping was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
4
9
0
Order By: Relevance
“…This younger age might influence their limited knowledge about their body. Despite the marked difference in the age of participants in these studies [24][25][26], they have similar findings with our study. Those found that the female participants' knowledge regarding the reproductive system was limited.…”
Section: Awareness Of Body Changes and Reproductive Health Literacysupporting
confidence: 90%
See 1 more Smart Citation
“…This younger age might influence their limited knowledge about their body. Despite the marked difference in the age of participants in these studies [24][25][26], they have similar findings with our study. Those found that the female participants' knowledge regarding the reproductive system was limited.…”
Section: Awareness Of Body Changes and Reproductive Health Literacysupporting
confidence: 90%
“…In this study we identified the gap in knowledge in both the reproductive body and pubertal body changes specifically among young female adolescents. There are several studies that used body mapping to explore female knowledge on their anatomy and physiology of reproductive system [24][25][26]. The finding of these studies were similar to our study in which female participants were shown to have limited understanding of their reproductive system.…”
Section: Awareness Of Body Changes and Reproductive Health Literacysupporting
confidence: 87%
“…This younger age might influence their limited knowledge about their body. Despite the marked difference in the age of participants in these studies (Cornwall, 1992;Kenny et al, 2019;Victora & Knauth, 2001), they have similar findings with our study. Those found that the female participants' knowledge regarding the reproductive system was limited.…”
Section: Awareness Of Body Changes and Reproductive Health Literacysupporting
confidence: 89%
“…In this study we identified the gap in knowledge in both the reproductive body and pubertal body changes specifically among young female adolescents. There are several studies that used body mapping to explore female knowledge on their anatomy and physiology of reproductive system (Kenny et al, 2019;Victora & Knauth, 2001). The finding of these studies were similar to our study in which female participants were shown to have limited understanding of their reproductive system.…”
Section: Awareness Of Body Changes and Reproductive Health Literacymentioning
confidence: 99%
“…Cambodian youth face numerous obstacles to sound sexual and reproductive health (SRH) including lack of SRH literacy and limited access to modern contraceptive methods [3]. Cambodia is lagging far behind neighbouring countries in the implementation of effective strategies for improving sexual and reproductive health (SRH) [4,5].…”
Section: Introductionmentioning
confidence: 99%